Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1017/s0033291722001775
|View full text |Cite
|
Sign up to set email alerts
|

Mediators and moderators in the relationship between maternal childhood adversity and children's emotional and behavioural development: a systematic review and meta-analysis

Abstract: Maternal experiences of childhood adversity can increase the risk of emotional and behavioural problems in their children. This systematic review and meta-analysis provide the first narrative and quantitative synthesis of the mediators and moderators involved in the link between maternal childhood adversity and children's emotional and behavioural development. We searched EMBASE, PsycINFO, Medline, Cochrane Library, grey literature and reference lists. Studies published up to February 2021 were included if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…These conditions can be further categorized into two distinct groups known as internalizing and externalizing problems [2]. The result of the study confirmed that childhood adversities can expose successive generations of families to the consequences of poorer health and vulnerability to behavioral and mental health problems [3].…”
Section: Introductionmentioning
confidence: 54%
“…These conditions can be further categorized into two distinct groups known as internalizing and externalizing problems [2]. The result of the study confirmed that childhood adversities can expose successive generations of families to the consequences of poorer health and vulnerability to behavioral and mental health problems [3].…”
Section: Introductionmentioning
confidence: 54%
“…Certain variables (e.g., maternal mind-mindedness, maternal sensitivity, maternal attachment styles) demonstrated significant effects when examined via more complex models. A similar review was recently conducted that examined the research question in the context of all children below the age of 18 years, 47 capturing less than half of the studies that this review included and also warranting caution when generalizing findings as development in preschool differs substantially from other developmental periods (i.e., teenage). Both reviews do however identify a pertinent role of maternal depressive symptoms/depression as a mediator of the association between maternal ACEs and children's behavioural problems.…”
Section: Discussionmentioning
confidence: 99%
“…Broad adoption of these newer findings is delayed in our field though. For example, in what appears to be the first systematic review and meta-analysis of mediators of the link between maternal childhood adversity and children's socioemotional and behavioral development (Ma et al, 2022), there is discussion of some evidence for antenatal or lifetime maternal depression and maternal perinatal health (e.g., gestational diabetes, abortion history and smoking during pregnancy) as mediators, but most associations reviewed in that paper well null, and prenatal programing was not mentioned/considered as a mediating process by the authors. Beyond the focus on children's mental health outcomes, however, scholars are paying increasing attention.…”
Section: Multiple Periods Of Maternal Adversitymentioning
confidence: 99%